THEORETICAL ANALYSIS OF THE COMBINED EXTRUSION OF THE FLANGE BY THE UPPER EVALUATION METHOD IN THE MANUFACTURE OF THE “PICABUR BODY” PRODUCT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article talks about the work that is being carried out in the field of design and production of tools for drilling rocks. Formulas of combined extrusion by the method of upper evaluation of an axisymmetric product are given. The results of extrusion of the Picabur body, the scheme of combined extrusion with flange sediment are shown.